Pengaruh Religiusitas, Promosi, Dan Pelayanan Dalam Pengambilan Keputusan Menjadi Nasabah Tabungan Haji Pada PT. Bank Muamalat Cabang Mamuju - Aco, Nur Asia; Natasya, Natasya (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
This study aims to determine the significant influence of religiosity on the decision to become a Hajj savings customer at Bank Muamalat Mamuju Branch Office. To find out the significant effect of Promotion on the decision to become a Hajj savings customer at Bank Muamalat Mamuju Branch Office and to determine the significant effect of Service on the decision to become a Hajj savings customer at Bank Muamalat Mamuju Branch Office. Sources of data used in this study are quantitative data and qualitative data. Data sources are primary and secondary data. Religiosity significantly influences the decision to become a customer in choosing Hajj savings at Bank Muamalat Mamuju Branch by obtaining a tcount value of 4.753 which is greater than the ttable value of 1.994 and a significant value of 0.000 less than 0.05, thus the hypothesis is accepted. Promotion has a significant effect on the decision to become a customer in choosing Hajj savings at Bank Muamalat Mamuju Branch with the acquisition of a tcount value of 4.192 greater than the ttable value of 1.994 and a significant value of 0.000 less than 0.05, thus the hypothesis is accepted. The service has a significant effect on the decision to become a customer in choosing Hajj savings at Bank Muamalat Mamuju Branch with the acquisition of a tcount value of 3.267 which is greater than the ttable value of 1.994 and a significant value of 0.002 less than 0.05, thus the hypothesis is accepted..